Role of Inflammation and Tumor Microenvironment in the Development of Gastrointestinal Cancers: What Induced Pluripotent Stem Cells Can Do? - Zhang, Lei; Song, Xiaojing; Mohri, Yasuhiko; Qiao, Liang (Current Stem Cell Research & Therapy, 2015)
Connections between inflammation and cancer are a rapidly developing field. Some gastrointestinal tract cancers arise from infection, chronic irritation, and ensuing inflammation. Cellular effectors and mediators are important constituents of the tumor microenvironment, including neoplastic, stromal, and migratory hematopoietic cells. Complex interaction between these cells in the tumor microenvironment regulates tumor growth, progression, metastasis, and angiogenesis. Tumor-associated macrophages represent the major inflammatory cell population in tumors, which orchestrate various aspects of cancer. Cytokines and chemokines are major mediators of communication between cells in the tumor microenvironment. The concept of oncogene builds up an inflammatory pre-neoplastic microenvironment has emerged in the last few years. On the other hand, the development of induced pluripotent stem cells (iPSCs) unraveled a mystery in stem cell research. However, there are still some debates about iPSCs which should be answered by science.
Keywords: inflammation